NyaYa: Blockchain-based electronic law record management scheme for judicial investigations. (December 2021) - Verma, Ashwin; Bhattacharya, Pronaya; Saraswat, Deepti; Tanwar, Sudeep
Abstract: In digitization, judicial investigations have transitioned towards digital storage of forensic shreds of evidence as electronic law records (ELRs). The shift poses varied challenges of ELR preservation, homogeneity of case formats, chronology in recorded statements by suspects, time-stamping and digital signatures on ELRs, and the chain of transfer of cases to different law enforcement agencies (LEAs) over open channels. Thus, privacy and trust among judicial stakeholders-case appellant (CA), case defendant (CD), the police officer (PO), defence lawyer (DL), prosecutor lawyers (PL), LEAs, and court judge is a prime concern. Motivated from the aforementioned discussions, the paper presents a blockchain (BC)-based ELR management scheme, NyaYa, that operates as a four-phased scheme of judicial stakeholder registration in BC, case registration with meta-hash keys in public BC, that reference an external off-chain interplanetary file storage (IPFS), chronology of investigative updates among LEAs, and case hearing and settlement through smart contracts (SCs). In the simulation, NyaYa is compared to traditional ELR storage schemes for parameters like mining cost, query fetching time, block processing time, obtained IPFS throughput, signing latency, the effect of collusion attacks, ELR processing time, and corrupted indexes in IPFS. We also presented formal verification and proposed functionalities of SCs. In simulation, at 6 USD mining cost, NyaYa can append 22456 transactions, compared to 21497 and 3000 transactions respectively in existing schemes. The achieved query fetching time is 0.852 milli-seconds (ms), at 25 blocks, with cache support of 32 kilobyte (KB). The scheme has an average signing latency of 622 . 95 ms, and achieves a high-trust probability of 0.887 %, compared to 0.765 % in consortium BC, and 0.455 % in private BC, at 500, colluding nodes. An improvement of 6.77 % is achieved in ELR uploading latency, and the scheme has only 21 corrupted IPFS indexes for 350 fetched ELRs. The obtained results indicate the efficacy of the proposed scheme against conventional schemes.